Partial tendon tear as unusual cause of trigger finger: a case report. Issue 1 (1st January 2016) - Calderaro, Cosma; Guzzini, Matteo; Pagnottelli, Marco; Fabbri, Mattia; Perugia, Dario
Abstract: We report a case of post-traumatic trigger finger due to a partial longitudinal tear of the flexor digitorum superficialis. The suspect came from the clinical history and the young age of the patient. It was successfully treated with tendon flap suture and pulley A1 release.